2010
DOI: 10.3184/003685010x12800828155007
|View full text |Cite
|
Sign up to set email alerts
|

Properties and applications of Zeolites

Abstract: Zeolites are aluminosilicate solids bearing a negatively charged honeycomb framework of micropores into which molecules may be adsorbed for environmental decontamination, and to catalyse chemical reactions. They are central to green-chemistry since the necessity for organic solvents is minimised. Proton-exchanged (H) zeolites are extensively employed in the petrochemical industry for cracking crude oil fractions into fuels and chemical feedstocks for other industrial processes. Due to their ability to perform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
80
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(84 citation statements)
references
References 188 publications
0
80
0
4
Order By: Relevance
“…[91] These authors showedt hat the withdrawal of electronic chargef rom the linker leads to enhanced acidity for the hydrogena toms on the linker,w hich can form weakh ydrogen-bond interactions with the oxygen atoms of CO 2 .T hey also found that the binding capacity of the linker with an itro functional group for CO 2 is much higher,o wing to the strong effect of the nitro group on polarizing the CO 2 molecule. To rrisi et al [92] studied the effect of introducingp olar groups (NO 2 , NH 2 ,O H, SO 3 H, and COOH)i nto benzene linkers. They showed that the strongest interaction is with the lone-pair-donation atoms (N, O) of the side groups.…”
Section: Enthalpic Separation Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…[91] These authors showedt hat the withdrawal of electronic chargef rom the linker leads to enhanced acidity for the hydrogena toms on the linker,w hich can form weakh ydrogen-bond interactions with the oxygen atoms of CO 2 .T hey also found that the binding capacity of the linker with an itro functional group for CO 2 is much higher,o wing to the strong effect of the nitro group on polarizing the CO 2 molecule. To rrisi et al [92] studied the effect of introducingp olar groups (NO 2 , NH 2 ,O H, SO 3 H, and COOH)i nto benzene linkers. They showed that the strongest interaction is with the lone-pair-donation atoms (N, O) of the side groups.…”
Section: Enthalpic Separation Mechanismsmentioning
confidence: 99%
“…[22] There is ac onceptual differenceb etween adsorption of small versus large molecules. In contrastt ol arger molecules, small gas molecules such as CO 2 ,O 2 ,N 2 ,a nd CH 4 have little or no shape/size differences relative to the framework. They behavem ore like af luid inside large pores of nanoporous materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…applications such as water purification and softening, separation of gases, nuclear industry, and sensors (6)(7)(8)(9)(10)(11)(12)(13)(14). They can also act as suitable supports for immobilization of enzymes (15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Zeolites are naturally occurring crystalline aluminum-silicates that are used for lon exchange, gas adsorption and water adsorption, with the unique property that they can remove contaminants using anion exchange and then be recharged and reused (Rhodes, 2010). Fly ash can be converted into low grade zeolites, which are particularly well suited for the removal of phosphates and heavy metals from wastewater.…”
Section: Zeolite Manufacturementioning
confidence: 99%